TimeTree 5: An Expanded Resource for Species Divergence Times - Kumar, Sudhir; Suleski, Michael; Craig, Jack M; Kasprowicz, Adrienne E; Sanderford, Maxwell; Li, Michael; Stecher, Glen; Hedges, S Blair (Molecular biology and evolution, 2022)
Abstract We present the fifth edition of the TimeTree of Life resource (TToL5), a product of the timetree of life project that aims to synthesize published molecular timetrees and make evolutionary knowledge easily accessible to all. Using the TToL5 web portal, users can retrieve published studies and divergence times between species, the timeline of a species’ evolution beginning with the origin of life, and the timetree for a given evolutionary group at the desired taxonomic rank. TToL5 contains divergence time information on 137,306 species, 41% more than the previous edition. The TToL5 web interface is now Americans with Disabilities Act-compliant and mobile-friendly, a result of comprehensive source code refactoring. TToL5 also offers programmatic access to species divergence times and timelines through an application programming interface, which is accessible at timetree.temple.edu/api. TToL5 is publicly available at timetree.org.